Dates and guava to increase hemoglobin levels in adolescent girls - Nori Yulia Ningsih; Nike Sari Oktavia; Faridah BD (Jurnal Kesehatan Ibu dan Anak, 2021)
Iron deficiency causes decreased learning enthusiasm, tired and insomnia in adolescent girls. The purpose of this study was to determine the differences in the effect of dates and guava fruit on increasing haemoglobin levels on adolescent girls. This type of research is pre experiment with the design of two groups pretest and posttest desaign. The study was conducted in November 2019–11 April 2020 at the Bina Harapan Salido Foundation, Padang, Indonesia. The sampling used purposive sampling technique and the Roscoe formula with a sample of 20 adolescent girl. The instrument used was Hb digital hemosmart and observation sheets. Processing of test data T test dependent and independent. The average levels of haemoglobin before being given dates 11.200 g/dl (minimum 10.3 g/dl, maximum 11.9 g/dl) and after being given dates 12.500 g/dl (minimum 11.5 g/dl, maximum 13.6 g/dl), while the average haemoglobin level before being given guava was 11.190 g/dl (minimum 10.6 g/dl, maximum 11.8 g/dl) and after being given guava 12.170 g/dl (minimum 11.2 g/dl, a maximum of 13.1 g/dl). There was different of haemoglobin levels before and after being given dates (Mean different= 1.300; SD= 0.563; 95% CI =0.89-1.10; p-value=0.000). There was different of  haemoglobin levels before and after being given guava (Mean different= 0.980; SD= 0.367; 95% CI =0.71-1.24; p-value=0.000). There was no difference in the effect of dates and guavas on the increase in haemoglobin levels (p-value=0.150). There was an effect of dates and guavas on increasing haemoglobin levels, but there was no difference in the effect of dates and guavas on increasing haemoglobin levels.